PENYULUHAN BANK SAMPAH - Yayuk Minta Wahyuningsih; Zuraida (Fakultas Pertanian UVAYA Banjarmasin, 2025)
Solution to achieve a clean and comfortable settlement for its citizens can with Carbage Banks. With this pattern, apart from being disciplined in managing waste, residents also get additional income from the collected waste. While the benefits of the Garbage Bank are reducing the amount of waste in the community environment, creating a clean, healthy environment and fostering public self-awareness of the importance of protecting and respecting the environment. The Garbage Bank by implementing the 3R concept is the concept of collecting household dry waste, such as plastic, paper, cans etc. which implements a conversion system from waste to money, to increase citizen participation in sorting and recycling waste. And there is organic waste management in the form of kitchen waste and leaves that can be used as compost for plants. The way the waste bank system works is that the garbage bank has officers who work to weigh waste, officers who record the weight of waste deposited by members, savings managers who record the results of deposits and the last is officers who negotiate with garbage collectors or environmental offices and then receive the money